Comparison of ergometer- and track-based testing in junior track-sprint cyclists. Implications for talent identification and development. Issue 19 (2nd October 2017) - Tofari, Paul J.; Cormack, Stuart J.; Ebert, Tammie R.; Gardner, A. Scott; Kemp, Justin G.
ABSTRACT: Talent identification (TID) and talent development (TDE) programmes in track sprint cycling use ergometer- and track-based tests to select junior athletes and assess their development. The purpose of this study was to assess which tests are best at monitoring TID and TDE. Ten male participants (16.2 ± 1.1 year; 178.5 ± 6.0 cm and 73.6 ± 7.6 kg) were selected into the national TID squad based on initial testing. These tests consisted of two 6-s maximal sprints on a custom-built ergometer and 4 maximal track-based tests (2 rolling and 2 standing starts) using 2 gear ratios. Magnitude-based inferences and correlation coefficients assessed changes following a 3-month TDE programme. Training elicited meaningful improvements (80–100% likely) in all ergometer parameters. The standing and rolling small gear, track-based effort times were likely and very likely (3.2 ± 2.4% and 3.3 ± 1.9%, respectively) improved by training. Stronger correlations between ergometer- and track-based measures were very likely following training. Ergometer-based testing provides a more sensitive tool than track-based testing to monitor changes in neuromuscular function during the early stages of TDE. However, track-based testing can indicate skill-based improvements in performance when interpreted with ergometer testing. In combination, these tests provide information on overall talent development.